Development and preliminary evaluation of a patient portal messaging for research recruitment service. Issue 1 (25th May 2018) - Gleason, Kelly T.; Ford, Daniel E.; Gumas, Diana; Woods, Bonnie; Appel, Lawrence; Murray, Pam; Meyer, Maureen; Dennison Himmelfarb, Cheryl R.
Abstract : Introduction: We developed a service to identify potential study participants through electronic medical records and deliver study invitations through patient portals. Methods: The service was piloted in a cohort study that used multiple recruitment methods. Results: Patient portal messages were sent to 1303 individuals and the enrollment rate was 10% (n=127). The patient portal enrollment rate was significantly higher than email and post mail (4%) strategies. Conclusion: Patient portal messaging was an effective recruitment strategy.